Archaeometallurgical Investigations in Nakhchivan, Azerbaijan: What Does the Evidence from Late Chalcolithic Ovçular Tepesi Tell Us about the Beginning of Extractive Metallurgy?. (2nd November 2017) - Gailhard, Nicolas; Bode, Michael; Bakhshaliyev, Veli; Hauptmann, Andreas; Marro, Catherine
ABSTRACT: The Late Chalcolithic (4400–3950b.c. ) occupation levels from Ovçular Tepesi have yielded a significant assemblage of copper objects and remains of copper production. Together with ore finds, two fragments of nozzle, crucible remains, and a number of small metal artifacts, this assemblage includes the unexpected discovery of three copper axes in an infant burial jar. These axes are the earliest examples of large copper tools known to date in southwestern Asia, whether it is in the Caucasus, Iran, or the Anatolian highlands. More importantly, the fact that these objects were locally produced suggests that significant metallurgical activities were being carried out at Ovçular as early as the second half of the 5th millenniumb.c . After presenting the evidence from Ovçular Tepesi, this paper will proceed to a reassessment of the available archaeological and geochemical data concerning the emergence of extractive metallurgy in the southern Caucasus.